Crianças e infâncias: um estudo sobre a produção acadêmica dos programas de pós-graduação da UEA nas áreas de ciências humanas e ensino - Cruz, Bruna Beatriz de Oliveira (2022)
The present study aimed to know the academic production between the years (2018-2020) investigating researches with Amazonian children in the proposal to reflect how they contribute to constitute new conceptual perspectives on the terms "children" and/or "childhoods", fostering the understanding of the "Amazonian Childhoods" as a social construction. In the first chapter, an approach is made to the studies on the Sociology of Childhood, reflecting on the different social configurations that have been established for the subjects of this group. In chapter two, the proposed dialogue identifies the visibility of the Amazonian child by means of the researches found on this bias. The third and last chapter illustrates the discussions on the selected works conjecturing that these researches favor attributing new meanings to the images of the "Amazonian Childhoods". The methodological path was developed by mixed methods: qualitative and quantitative on the Dissertations of the Post-Graduation Programs in the areas of Humanities and Teaching of the Amazonas State University, PPGICH and PPGEEC. The interdisciplinary aspect used to reflect on the chosen productions provided the understanding that the perceptions of the Amazonian child dialog about symbolic trajectories of social invisibilities, in both studies the "Amazonian Childhood" is permeated by a forgetfulness of children's voices, however these researches reiterate the need for children who live in the Amazon to be recognized as subjects of rights and social agents protagonist of knowledge